2020
DOI: 10.3390/rs12244088
|View full text |Cite
|
Sign up to set email alerts
|

Navigation and Mapping in Forest Environment Using Sparse Point Clouds

Abstract: Odometry during forest operations is demanding, involving limited field of vision (FOV), back-and-forth work cycle movements, and occasional close obstacles, which create problems for state-of-the-art systems. We propose a two-phase on-board process, where tree stem registration produces a sparse point cloud (PC) which is then used for simultaneous location and mapping (SLAM). A field test was carried out using a harvester with a laser scanner and a global navigation satellite system (GNSS) performing forest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…They concluded that the addition of LiDAR contributed to an improvement of 38% compared to the traditional approach of only using GNSS+IMU. In [79], the authors proposed a SLAM method called sparse SLAM (sSLAM) whose main application is in forests and for sparse point clouds. They tested their method on the field with a LiDAR and a GNSS-mounted on a harvester and compared their method with LeGO-LOAM.…”
Section: Lidar Perceptionmentioning
confidence: 99%
“…They concluded that the addition of LiDAR contributed to an improvement of 38% compared to the traditional approach of only using GNSS+IMU. In [79], the authors proposed a SLAM method called sparse SLAM (sSLAM) whose main application is in forests and for sparse point clouds. They tested their method on the field with a LiDAR and a GNSS-mounted on a harvester and compared their method with LeGO-LOAM.…”
Section: Lidar Perceptionmentioning
confidence: 99%
“…Among these, only one paper exclusively uses passive RS data [21], while 29 papers use at least one LiDAR dataset in the analysis [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][22][23][24][25][26][27][28][29][30]. Ten papers exclusively use airborne laser scanning (ALS) data [4,6,7,10,11,13,18,23,26,27], nine papers exclusively use terrestrial laser scanning (TLS) data in the analysis [3,9,15,16,20,22,24,25,30], two papers exclusively use mobile laser scanning (MLS) data …”
mentioning
confidence: 99%
“…Finally, five papers use combined active and passive remote sensing data sets [2,14,17,19,28]. Regarding the scale of the analysis, 18 of the studies perform individual tree level (ITL) analysis [1][2][3][8][9][10][11][12][14][15][16]19,20,[23][24][25][26]30], eight papers report stand level (SL) analysis [6,7,17,18,21,22,27,29] and four report a combination of ITL and SL [4,5,13,28]. Tree position, diameter at breast height (DBH) and individual tree height (h) are the most common variables of interest, analyzed in nine, six and six papers, respectively, while the most commonly used methods are 3D reconstruction, point filtering and statistical modelling, which are used in eight, five and five papers, respectively (see Table 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations